2014
DOI: 10.1108/pr-09-2012-0156
|View full text |Cite
|
Sign up to set email alerts
|

Organizational rewards: considering employee need in allocation

Abstract: Purpose – The purpose of this study is to investigate how employee need relates to rewards and employee perceptions of fairness within an organization in the USA using a pay-for-performance system. Design/methodology/approach – To evaluate the presence of a relationship between employee need and reward allocation in a pay-for-performance system, a questionnaire was administered to a sample of 292 employees from two departments at an acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 67 publications
1
6
1
Order By: Relevance
“…However, subjective utility did not moderate the effects of the provision of all employee benefits. This goes against previous findings on the importance of employee needs for the outcomes of employee benefits (Day et al , 2014). Consequently, the usefulness of flexible (cafeteria) benefit plans that allow employees to choose employee benefits according to their preferences is not directly supported.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…However, subjective utility did not moderate the effects of the provision of all employee benefits. This goes against previous findings on the importance of employee needs for the outcomes of employee benefits (Day et al , 2014). Consequently, the usefulness of flexible (cafeteria) benefit plans that allow employees to choose employee benefits according to their preferences is not directly supported.…”
Section: Discussioncontrasting
confidence: 97%
“…Despite the call for further study of the effects of employee perspectives toward rewards (Xavier, 2014), available evidence on the effect of rewards utility on positive employee outcomes is limited and mostly focuses on monetary rewards, not employee benefits (Dulebohn et al , 2009). Research on the perceived utility of employee benefits is surprisingly limited (for example Day et al , 2014 focused on employee needs), and evidence on the ways that employee benefits can be grouped according to their subjective utility is not conclusive. The importance of determining employees’ benefit preferences was stressed in early studies of employee benefits and it has been the basis for the introduction of cafeteria/flexible benefits that have recently become very popular in HRM practice of companies (Hillebrink et al , 2008; Vidal-Salazar et al , 2016).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The effect of workload and lexible working hours are not signi icant. Findings of this study are in agreement with the indings of previous studies (Day et al, 2014;Njanja et al, 2013;Orpen, 1982;Sarwar & Abugre, 2013;Shahzadi et al, 2014;Sun & Bunchapattanasakda, 2019;Türk, 2008;Turk, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…These rewards and recognition motivate the employees and improve their performance (Shahzadi, Javed, Pirzada, Nasreen, & Khanam, 2014). Previous studies found that promotion, rewards, and recognition has a signi icant effect on the EP (Day, Holladay, Johnson, & Barron, 2014;Njanja, Maina, Kibet, & Njagi, 2013;Orpen, 1982;Sarwar & Abugre, 2013). Accordingly, in this study, it is proposed that promotion, rewards, and recognition have a signi icant effect on EP.…”
Section: Promotion Rewards and Recognition (Prr) And Epmentioning
confidence: 92%
“…Implementation of performance based pay can be realized through the effective performance based pay management strategy. Performance based pay management is normally described as a procedure of allocating pay in a systematic method, based on employees' knowledge, skill, and/or performance (Newman et al, 2017;Osterloh, 2014;Webb et al, 2014). The management of performance based pay has two main components: communication, and participation (Aimi, Azman & Fatmawati, 2014;Azman & Mohd Ridwan, 2017b).…”
Section: Introductionmentioning
confidence: 99%